Vegetation monitoring at Pueblo Chemical Depot: 1999-2015 - Rondeau, Renée J., author; Doyle, Georgia A., author; Decker, Karin, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2016)
In 1998 the U. S. Fish and Wildlife Service (USFWS) contracted the Colorado Natural Heritage Program to set up a long‐term vegetation monitoring program on U.S. Army Pueblo Chemical Depot (PCD) in Pueblo County, Colorado. PCD makes up the southern portion of an important landscape conservation area – Chico Basin – and monitoring data collected here can be useful to PCD land managers as well as regional land managers. The PCD monitoring program was established to detect vegetation changes in shortgrass prairie, sandsage shrubland, and greasewood shrubland as a result of the removal of cattle grazing in 1998. Each vegetation type included areas with four different historic cattle grazing regimes: 1) grazed year‐round until 1998, 2) grazed, but not year‐round, until 1998, 3) grazed lightly (several times/year) since 1942, and 4) ungrazed since 1942. For the purpose of this study the first two regimes are considered "grazed" and the latter two regimes "ungrazed." All further reference to the "grazed" regime refers to its historical use prior to 1998. During the 1999‐2015 years of monitoring neither grazed nor ungrazed study plots discussed in this report received any livestock grazing.
Prepared for: U.S. Fish & Wildlife Service, Colorado Fish & Wildlife Conservation Office, Pueblo Chemical Depot.
May 2016.